AN EXPLORATORY STUDY OF REMOTE OFFSHORE EMPLOYEE’S ENGAGEMENT: A STUDY ON NORTH SEA OFFSHORE REMOTE WORKFORCE - Beena, Manjusree (Digital Repository of Theses, 2022)
Popularly known as Oil capital of Europe, the Oil and Gas industry in the UK North Sea is an integral part of UK’s economic system contributing 49% of total offshore employment. Oil and Gas UK (OGUK) reports that economic downturn in the recent years and pandemic impacted the industry contributing to low employee – employer relationship, low engagement, and high turnover rate. Given the difficulties experienced within offshore industry, the research aims to explore the management and experience of employee engagement amongst offshore remote workforce in the North Sea offshore Oil and Gas industry. This is an exploratory study and to accomplish the research aim and objectives, both qualitative and quantitative approaches using interviews and questionnaire survey are used. Due to the diverse nature behind employee engagement, this research adopted a sequential mixed methods to examine employee engagement. The interview findings are used along with literature evidence to develop quantitative research. 7 interview participants and 70 questionnaire participants comprising Page 3 of 342 offshore remote workforce of different level positions from various Oil and Gas companies in the Northeast of Scotland have participated in the research study. Additionally, 3 interviews with senior leaders were also conducted. The questionnaire and interview participants were accessed via social media. The collected qualitative data were summarized to key points and key themes and patterns were explored. The interview data were analyzed using Braun and Clarke’s thematic analysis. The quantitative data were gathered through the questionnaire analysis. This research produced a number of key findings: (a) internal and external factors including organizational factors affect engagement drivers (b) the alignment between an employee’s values, their organization’s values and culture plays an important role in employee engagement (c) communication and keeping the employees informed of any organizational change plays a vital role in keeping employees engaged (d) to reduce attrition rates and retain passionate employees, effective management strategies should be executed into organizations. The main conclusion drawn from this research was that the current approaches used to drive employee engagement in the Oil and Gas industry should be revised. Greater efforts must be made to foster a trusting and quality relationship between employees and the organization. Key findings and recommendations from the research will contribute to the enhancement of employee engagement among offshore remote workforce.